Problems in the use of the photo-electric glottograph - Hutters, Birgit (Annual Report of the Institute of Phonetics University of Copenhagen, 1976)
This preliminary study originates in some of the recurrent problems encountered at this institute in the course of several years of working with the photo-electric glottograph. The relationship between the amplitude of the glottogram and the glottis aperture is studied by means of synchronous glottographic and fiberoptic recordings of the glottis during the articulation of long, unvoiced consonants in syllables with emphatic stress. According to this study, one does not very often find a linear relation between the glottis aperture and the amplitude of the glottogram. It is pointed out that the non-linearity may be caused by one or several factors affecting the amplitude of the glottogram. This non-linearity is crucial for the interpretation of the amplitude of the glottographic curve.